Factors Affecting the Performance of the Posbindu Program in the Padasuka Health Center - Tirta Adikusuma Suparto; Dayu Widayani; Asih Purwandari Wahyoe Puspita; Slamet Rohaedi; Syifa F Syihab; Andria Pragholapati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Posbindu is one of the services for elderly people at the community level to provide health services which include physical and mental emotional checks. Based on preliminary research in February 2020 at Puskesmas Padasuka, Bandung City, there are 4 Posbindu whose existence is less attractive to each elderly so they cannot describe optimal benefits. The purpose of this research is to explore the factors that influence the performance of the Posbindu program at Puskesmas Padasuka, Bandung City. The research design used in this research is qualitative with a case study approach conducted from March to September 2020. Sampling using purposive sampling with the sample criteria is Posbindu which has separate application from Posyandu infants, namely at 4 Posbindu. The results of the research show that the Posbindu program is influenced by factors, namely: 1) inadequate budget for implementing the Posbindu program, 2) lack of guidance for Posbindu cadres, 3) low knowledge and skills of cadres in carrying out health education, 4) facilities and infrastructure at Posbindu which is inadequate, 5) inadequate physical and emotional checks, 6) lack of health counseling for the elderly and their families, 7) lack of simple treatment, 8) low levels of elderly visits to Posbindu, and 9) less optimal contribution of Posbindu to the elderly age. Revitalization efforts are one of the interventions that can be done to overcome these factors.